ҚАРАҚАЛПАҚ ТИЛИНДЕГИ АФФИКС МОРФЕМАЛАРДЫҢ ТҮРЛЕРИ - Оразымбетов, А.Қ. (ILIM hám JÁMIYET, 2024)
This article deals with the presence in affix morphemes of the modern Karakalpak language, depending on their place in the structure of the word, in addition to suffixes, postfixes, prefixes, inflections, there are also interfixes, infixes, and unifixes. Stating that each of them requires a separate study, interfixes, infixes, and unifixes are explained with theoretical explanations and examples.